EFEKTIVITAS KERJA ROOM ATTENDANT DI KHAS HOTEL PEKANBARU - Agustin, Ananda Nella; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study aims to determine the effectiveness of the room attendants work at Khas Hotel Pekanbaru. This study uses a quantitative method with a quantitative descriptive research design. The population of this study is all housekeeping employees in the room section, totaling 5 room attendants. Because the population is small, the researcher used total sampling. Research data were collected through observation, interviews and documentation. The study was conducted with observations for 3 working days and 3 days off. The results of the study showed that the average percentage achieved by room officers on weekdays was 97.8% while the average percentage achieved by room officers on weekends was 98.47%. Based on these results, it can be concluded that the effectiveness of room officers at Khas Hotel Pekanbaru is effective. The consistency of room officer performance is also very good on weekdays and weekends despite differences in workload (occupancy). Keywords: Work Effectiveness, Room Attendant, Housekeeping